Pengembangan Panduan Motivasi Diri Dengan Kegiatan Grebeg Suro sebagai Wujud moderasi beragama di Desa Sukoreno Kecamatan Umbulsari Kabupaten Jember Tahun 2025 - Puji Maulana (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This research aims to develop a research guidebook product related to students' self-motivation in elementary schools, with the aim of finding out the extent of the role of the gerebeg suro event in increasing students' self-motivation at the Sukoreno 01 state elementary school in increasing awareness of religious moderation in the community, especially in Sukoreno Nang village, which incidentally is a Pancasila village, a village with various religions and cultures in Jember district. upaten Jember. With a background of various religions including Christianity, Hinduism, Islam and beliefs in Sukoreno village, giving rise to various cultures and patterns of society in the village, based on the above, awareness is needed in religious moderation. With good self-motivation, a style of social life that is aware of moderation in religion and society will be realized. Data analysis using the development model used in developing this self-motivation guide is a modification of the Borg and Gall (1983) model. According to Borg and Gall (1983), research and development (R&D) procedures consist of two main objectives, namely: (1) developing products, and (2) testing the effectiveness of products in achieving goals. The first objective is referred to as the development function, while the second objective is referred to as the validation function. The development process usually stops at the stage of producing a product through limited trials, but such a product cannot be widely used, so the product needs to be validated. This validation step is intended to reduce uncertainty